The indices interconnection of Greco-Roman style wrestlers functional and technical-tactical readiness - Kuznetsov, A. S.; Mubarakzyanov, R. B. (The Russian Journal of Physical Education and Sport, 2017)
The rules of competitive combat organization are closely connected with tactical and technical elements of Greco-Roman wrestling. Many researchers and practicians claim that the rules of competitions change considerably influenced the quality of wrestling, which demands great changes in methodology of training sportsmen for competitive activity. Research methods: scientific-methodical literature analysis and summarizing, competitive activity analysis, correlation analysis of functional and technical-tactical readiness indices among Greco-Roman style wrestlers. Materials. The article deals with the questions of Greco-Roman style wrestlers` adaptation to the rules of competitions change; the results of correlation analysis of Greco-Roman style wrestlers` technical-tactical and physical readiness are presented. Results. Correlation analysis showed that high sports results achievement is connected with the indices, which characterize the process of training adaptation among Greco-Roman style wrestlers to the rules of competitions change. Conclusion. The increase of the revealed valid correlation connections verification in the experimental group after the experiment between the indices of technical-tactical readiness and the indices, which characterize special physical readiness, a functional state, spare capacities, physical working capacity and aerobic productivity, proves the fact that high sports results achievement is connected with the indices, which characterize the process of technical-tactical and functional readiness optimization among Greco-Roman style wrestlers on the basis of taking into account competitions rules change.